Prediksi Kesetimbangan Cair-Cair pada Sistem Air + Asam Format + Pelarut Organik dengan Model UNIFAC - Azaim, Ahmad Hayiz; Ramadhani, Farah Amirah Firyal; Altway, Saidah (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Formic acid can be produced by a fermentation process, producing an aqueous solution in the form of a fermentation broth. The separation of formic acid from water is challenging due to the presence of an azeotropic mixture. The aim of this research is to predict the liquid-liquid equilibrium data using the universal functional activity coefficient (UNIFAC) model for formic acid + organic solvent + water systems at 298.15 and 323.15 K and atmospheric pressure (101.3 kPa). The liquid-liquid equilibrium data are required as a reference for optimal design of formic acid extraction process. This research also introduces new two-phase systems for the separation of formic acid from aqueous solution and expands the scope of thermodynamic studies on formic acid extraction. The extraction performance was in the order of MIPK > 2-hexanone > MIBK. The temperature has no significant influence on the extraction performance. The prediction of formic acid + water + MIBK system at 298,15 K and atmospheric pressure (101.3 kPa) was also compared with the experimental data with the RMSD 9,76 %. This result represented that UNIFAC was a reliable model for the prediction of liquid-liquid equilibria of system involving formic acid.